Challenges of using protein antibiotics for pathogen control. Issue 9 (26th February 2021) - Chai, Ray; Rooney, William M; Milner, Joel J; Walker, Daniel
Abstract: Bacterial phytopathogens represent a significant threat to many economically important crops. Current control measures often inflict harm on the environment and may ultimately impact on human health through the spread of antibiotic resistance. Antimicrobial proteins such as bacteriocins have been suggested as the next generation of disease control agents since they are able to specifically target the pathogen of interest with minimal impact on the wider microbial community and environment. However, substantial gaps in knowledge with regards to the efficacy and application of bacteriocins to combat phytopathogenic bacteria remain. Here we highlight the immediate challenges the community must address to ensure maximum exploitation of antimicrobial proteins in the field. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Narrow‐spectrum antimicrobials like bacteriocins are a promising and sustainable alternative for controlling bacterial crop diseases. Here, we highlight the challenges that must be addressed to enable such protein antibiotics exploitation.